Initial outpatient clinical characteristics associated with subsequent conversion from mild cognitive impairment to dementia: A retrospective exploratory study - Natsuko Arimatsu; Marin Okada; Aya Matsumura; Shigeki Hirano; Ayumi Amemiya (Aging Clinical and Experimental Research, 2026)
Abstract Background Mild cognitive impairment (MCI) may progress to dementia, and clinical characteristics present at the initial visit may help inform follow-up and supportive care. Aims To explore initial-visit clinical characteristics associated with subsequent conversion to dementia in patients with MCI. Methods This retrospective exploratory study included patients diagnosed with MCI at their initial visit to a university hospital dementia outpatient clinic between 2012 and 2021. Patients were classified into converter and non-converter groups according to clinical outcomes during follow-up. Medical-record data were compared using the Mann–Whitney U test and Fisher’s exact test. Sensitivity analyses were also conducted to examine the influence of follow-up duration on the findings. Results Of 277 patients with MCI, 28 converted to dementia, with a median time to diagnosis of 497 days. The primary analysis compared these 28 converters with 30 non-converters followed for more than 497 days without a dementia diagnosis. Converters were older and less likely to report subjective memory complaints. Changes in “cooking and eating” and “money management” were more frequent among converters. They also had higher Functional Assessment Staging scores and lower Mini-Mental State Examination and Addenbrooke’s Cognitive Examination III scores. Behavioral and psychological symptoms did not differ significantly. Some findings varied across sensitivity analyses. Discussion Differences in subjective memory complaints, daily functioning, and neuropsychological performance may already be present at the initial visit, although their consistency depended partly on the definition of non-conversion. Conclusions Routinely collected outpatient information may help inform clinical assessment, follow-up planning, and supportive care in patients with MCI.